Hubungan Antara Pengetahuan, Peran Keluarga Dan Sumber Informasi (Media) Dengan Perilaku Seksual Remaja Pranikah Di SMP 1 Parang Kabupaten Magetan - Puspitasari, Rima Mailani; , Anisa Catur Wijayanti, S.K.M., M.Epid; , Farid Setyo Nugroho, S.K.M (2015)
Adolescent sexsual behavior that is risky among teenagers especially unmarried teens is increasing. This study aims to determine the relationship between knowledge, the role of the family, and sources of information (the media) with a premarital adolescent sexsual behavior in the junior 1 Parang Magetan. This study was an observational study with cross-sectional and quantitative method approach. Subjects were adolescents aged 12-15 years in junior hight school 1 Parang. Population in this research is class VII, VIII, and IX were in junior hight school 1 Parang the number of 629 student sampel used. The sampling techniqued used is propotional ramdom sampling. The statistical analysis used was Chi Square test with a confident lavel of 0,05. Research results get is a relationship between knowledge (p value=0,012 ; PR = 2,026 ; 95% CI : 1,256-3,237 ; CC : 0,257). the role of families (Pvalue=0,016 ; PR = 1,994 ; 95% CI : 1,165-3,413 ; CC : 0,246) and no connection between the sources of information (the media) (p value = 0,464) with sexsual behavior adolescent premarital in junior hight school 1 Parang district Magetan. Key words : Behavior, Premarital sexsual, Junior teens